Workers’ behavior and Forced Vital Capacity (FVC) batik workers in Batik Jetis Village, Sidoarjo - Arfiani, Novi Dian; Azizah, R.; Nugroho, Mohammad Apriyan; Jalaludin, Juliana (Universitas Airlangga, 2023)
Introduction: Batik is the art of drawing on the surface of the cloth. The process of making batik can cause problems for worker’s health. Batik workers interacted directly with chemical materials when producing batik and this material was dangerous for their health. This study aims to determine the behavior and Forced Vital Capacity (FVC) of batik industry workers in Kampung Batik Jetis, Sidoarjo. Method: This research is an observational study with a cross-sectional study design. This research was conducted from August to October 2019, located in the batik industry of Batik Jetis Village, Sidoarjo sub-District, Sidoarjo District. The sample was taken by total sampling with Inclusion criteria are research subjects who had age more than 20 years old and willing to be a research sample. Samples consisted of 9 batik workers from Batik Jetis village. Data were collected by observation and interviews, and the measuring of Forced Vital Capacity (FVC) using a spirometer. Result: Showed that 66.67% of respondents are ≥50 years old, 66.67% respondents in the obese category, 77.78% respondents had worked for more than 10 years, 33.33% respondents with a duration of work> 8 hours/day, 77.78% did not have smoking behavior, only 1 respondent (11.11%) had abnormal FVC. Conclusion: In summary, increase of age, abnormal nutritional status, working period, long duration of exposure and smoking behavior can cause FVC abnormalities, while physical activity (sports) has a positive relationship to FVC.